2018
DOI: 10.2319/101517-694.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of the middle cranial fossa and central skull base following Herbst appliance treatment

Abstract: HA therapy did not produce clinically significant changes in the middle cranial fossa and central skull base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In this regard, Basion was landmarked in the multiplanar sections and prelabeled with a 0.2-mm spherical dot and inter-timing point-to-point displacement was assessed using the Q3DC extension of the software. 21 Displacement was considered as the linear projection in the multiplanar 2D Cartesian coordinates (X, Y, and Z) between time points. Positive and negative values (mm) indicated Basion displacement along the X, Y, and Z coordinates according to the following pattern:…”
Section: Step 3 Basion Displacement Measurement and Euclidean Distances Registrationmentioning
confidence: 99%
“…In this regard, Basion was landmarked in the multiplanar sections and prelabeled with a 0.2-mm spherical dot and inter-timing point-to-point displacement was assessed using the Q3DC extension of the software. 21 Displacement was considered as the linear projection in the multiplanar 2D Cartesian coordinates (X, Y, and Z) between time points. Positive and negative values (mm) indicated Basion displacement along the X, Y, and Z coordinates according to the following pattern:…”
Section: Step 3 Basion Displacement Measurement and Euclidean Distances Registrationmentioning
confidence: 99%
“…Recent three‐dimensional (3D) study 21 concluded that Herbst appliance therapy did not produce clinically significant changes in the middle cranial fossa and central skull base.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MCF alignment determines nasomaxillary positioning and the changes in the middle cranial fossa and central skull base relative protrusive or retrusive effects of the maxilla and mandible. 19,20 Recent three-dimensional (3D) study 21 concluded that Herbst appliance therapy did not produce clinically significant changes in the middle cranial fossa and central skull base.…”
Section: Introductionmentioning
confidence: 99%